Improving the Quality of Public Services to Build Public Trust in Service Providers of the Health Sector - Yulianto, Yulianto (LPPM Institut Pendidikan Nusantara Global, 2024)
Services in the health sector are a real form of public service. Health is an investment for the country to carry out development because it requires human resources who are physically and spiritually healthy as well as to realize successful public services in the health sector which can have a positive impact in other fields. The quality of health services is very important within the scope of Public Administration because improving health services will support efforts to improve community welfare. However, in reality, what is happening in the field is that there are still many complaints from the public regarding the unequal quality of health services in Indonesia. Many people still complain about health procedures that are complicated, long, expensive and the poor behavior of health workers, so it is not surprising that more and more Indonesians prefer to go abroad to get medical treatment. This research aims to answer the question of why more and more Indonesians choose to seek treatment abroad and what efforts must be made to gain the trust of the Indonesian people in health service providers. This is qualitative research with a phenomenological approach. Data collection was carried out through semi-structured interviews with 10 patients who had sought treatment abroad several times and 1 representative from the Ministry of Health. The results of this research show that the reason why many Indonesians still seek treatment abroad is because the quality of health services in Indonesia is still low.